Preparation and characterization of PVDF-HFP/MG49 based polymer blend electrolyte - Ataollahi N.; Ahmad A.; Hamzah H.; Rahman M.Y.A.; Mohamed N.S. (2023)
Solid polymer electrolytes comprising poly (vinylidene fluoride-hexafluoro propylene) (PVDF-HFP), Poly (methyl methacrylate)-grafted natural rubber (MG49) and lithium salt (LiBF 4) were prepared by solution casting technique. The membranes were characterized by impedance spectroscopy (EIS), fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD) and scanning electron microscopy (SEM). The electrolyte exhibited the highest room temperature conductivity 2.810 _4 S cm -1 at 30 wt. % of LiBF 4. The conductivity increases with temperature but it does not obey Arrhenius rule. The interaction between lithium ions and polymer host was confirmed by fourier transform infrared spectroscopy. The XRD result confirmed that adding salt led to decrease the degree of crystallinity. The SEM studies showed that the morphology improved in the presence of the salt. 2012 by ESG.